PENANGANAN PASCAPANEN JERUK SIAM (Citrus nobilis var. microcarpa) TUJUAN PASAR SWALAYAN - Endang Christine Purba; Bambang S. Purwoko (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2019)
Citrus Siam (Citrus nobilis var. microcarpa) is a horticultural commodity that is widely consumed by Indonesian people. In addition to practically obtained, siam citrus also have a good nutritional content for human diet. This causes Indonesian markets always strives to meet the needs of consumers obtained from the producers of the citrus. However, in its distribution, the citrus siam experiences post-harvest handling which results in post-harvest losses. To find out the marketing chain of siam distribution and the loss of its crops, a research was conducted to investigate the situation in North Sumatra. A total of 37 citrus farmers in Simpang Empat and Payung Sub-districts were interviewed for data collection. In addition, gatherers,marketsuppliers and supermarkets are also interviewed as informants in this study. This research used direct interview method to respondents and direct observation at activity location of informants.The data analysis used descriptive analysis. Stages of post-harvest handling of citrus siam vary by point of marketing. The process of post-harvest handling of citrus siam is cleaning, sorting, grading, packaging, storage and transportation. The process of post harvest handling is done at the level of farmers, market suppliers and supermarkets. Total losses of the largest was at the farmer level of 5.6% while the smallest yield loss was at the supermarket level of 0.5%. This is due to the preparation of small citrus siam at the very bottom of the bamboo packaging and large fruit packing at the top. Keywords: citrus, farmers, loss of crops, post-harvest handling